# x^2+14x+49=0

## Simple and best practice solution for x^2+14x+49=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for x^2+14x+49=0 equation:

Simplifying x^{2}+ 14x + 49 = 0 Reorder the terms: 49 + 14x + x^{2}= 0 Solving 49 + 14x + x^{2}= 0 Solving for variable 'x'. Factor a trinomial. (7 + x)(7 + x) = 0## Subproblem 1

Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7## Subproblem 2

Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7## Solution

x = {-7, -7}

### See similar equations:

| x^2+16x+64=0 | | 4x^2=20x-25 | | 6x^2+9p-45=0 | | 6p^2+9p-45=0 | | 16a^3-4a^2+64a+36=0 | | 6x^2-19x+14=0 | | x^2+2x=A(x^2-2)+(Bx+C)(2x-4) | | 35x^2-18x-5=0 | | 5x^2+9x+4=0 | | x^2+2x=Ax^2-2A+2Bx^2-4Bx+2Cx-4c | | 20t^2-11t=3 | | 81t^2-25=0 | | x^2+8x-10=0 | | 3x^2+10x+2=0 | | 10c^2-29c+10= | | 14x^2-6x=0 | | 4x^2-11x-8=0 | | 6x^2+9x+1=0 | | 8x^2=24 | | X^2-3x+3=6+3 | | 2x^2-4x-8=-x^2+x | | x^2+x+9=0 | | (2x^2)-6x+15=0 | | K^2=13 | | y=(3m+7)*(m^2+13m-9) | | y=(m^2+4m-9)+(3m+7) | | y=(m^2-4m+9)+(3m+7) | | y=(m^3+4m^2-9m)+(3m+7) | | y=(m^3+4m^2-9m)*(3m+7) | | y=(3m+7)*(m^2-4m+9) | | y=(3m+7)*(m^2+4m-9) | | H^4+5=9 | | 5=m^3-9 | | 0=7u^3+14u^2 | | 0=12a^3-6a^2+18a | | 6x^2=x(9x+13)-2(x^2-x+8) | | 12x+5=-26x^2+x+20 | | x^2-5x+5=0 | | 23x^2-25x=0 | | 8x^2+18x-10=0 | | (6a^4b^4+5ab)+(2ab-6a^4b^4)= | | 45x^3+69x^2-13x-5=0 | | 3x^2-28x=0 | | x^2-4x-12=0 | | x^2+2x-3=0 | | x^2-4x-32=0 | | x^2-9x+20=0 | | 12x^5y=0 | | 15x^4y^6=0 | | X^2=6 | | 3d^2-5d-8=0 | | 5g^2+29g-6=0 | | x^3-6x^2=0 | | 3a^2-5a+2=0 | | 2x^2=18 | | x^2+0.9*x-0.2=0 | | 5x^2+2x-1=0 | | x^2+0.54*x-0.02=0 | | 9t^2-4= | | x^2+1.5*x-0.6=0 | | 6k^2-k-35=0 | | 4m^2-16m=0 | | u^3-7u^2=0 | | 17x^2-51x+34=0 | | x^2-2x+4=0 |